Analysis of Teacher’s Role in Freedom Writers Film - Dewa, Dewa Ayu Ratih; Wedayanthi, Luh Made Dwi; Suardana, I Putu Oka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the importance of the teacher's role in creating a meaningful learning process, as depicted in the film